2021
DOI: 10.5324/nje.v29i1-2.4047
|View full text |Cite
|
Sign up to set email alerts
|

An 11-year nationwide registry-linkage study of opioid maintenance treatment in pregnancy in Norway

Abstract: Aim: We aimed to describe opioid maintenance treatment (OMT) to pregnant women in Norway and study thebackground characteristics of the pregnant women compared to the general population of pregnant women andto a previous clinical cohort study of OMT in pregnancy.Methods: Population-based cohort study with linked data from the Norwegian Medical Birth Registry, theNorwegian Prescription Database, the Norwegian Patient Registry, and Statistics Norway. The study populationconsisted of women giving birth between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…29 Collectively, it is probable that the drug dose burden on the foetal brain might influence a child's functional outcome. The mean methadone and buprenorphine doses, 85 mg and 13 mg, respectively, in our study are comparable to doses of 85 mg methadone and 15 mg buprenorphine reported in a Norwegian register study, 30 and a Swedish study, 25 reflecting a relatively high common Scandinavian dose regime.…”
Section: Discussionsupporting
confidence: 84%
“…29 Collectively, it is probable that the drug dose burden on the foetal brain might influence a child's functional outcome. The mean methadone and buprenorphine doses, 85 mg and 13 mg, respectively, in our study are comparable to doses of 85 mg methadone and 15 mg buprenorphine reported in a Norwegian register study, 30 and a Swedish study, 25 reflecting a relatively high common Scandinavian dose regime.…”
Section: Discussionsupporting
confidence: 84%
“…As opposed to other countries, Norway has a law that protects the foetus; if any illicit drug use is considered to harm foetal health; the mother will be treated in an inpatient clinic, either voluntarily or under duress. Of additional importance is that most OMT women in Norway (85%–90%) are already in OMT before they become pregnant (Odsbu et al, 2021). Taken together, this may explain the lower prevalence of polydrug use (21%) and alcohol (8%) in this study compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, OMT in Norway includes ∼8,000 individuals, onethird being women. The number of pregnancies in the OMT program has been low and stable in the period 2005-2015 with a mean number of 28 pregnancies per year, representing 0.06% of the general pregnant population in Norway during the same time period (34).…”
Section: Methodsmentioning
confidence: 99%